2023
DOI: 10.3390/f14040714
|View full text |Cite
|
Sign up to set email alerts
|

CiteSpace Software Visualization Analyses of the Last Thirty Years of Research on Populus euphratica

Abstract: Populus euphratica is the only tall tree species that adapts to the desert environment. It has strong drought tolerance and is the subject of extreme concern at home and abroad. After 30 years of development, the scope of research on Populus euphratica is very extensive, but the research content has not yet been crystalized into a mature field, and research directions at home and abroad differ. In this study, we retrieved research references on ‘P. euphratica’ published from 1992 to 2022 in both the China Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…By analyzing the keyword burst (the keywords with a large change in frequency within a short time) in a large number of literature, CiteSpace could clearly show the research fronts/research hotspots in the field (Huang et al 2023 ). Hence, nodes with high-frequency keywords are considered cutting-edge content within their field.…”
Section: Resultsmentioning
confidence: 99%
“…By analyzing the keyword burst (the keywords with a large change in frequency within a short time) in a large number of literature, CiteSpace could clearly show the research fronts/research hotspots in the field (Huang et al 2023 ). Hence, nodes with high-frequency keywords are considered cutting-edge content within their field.…”
Section: Resultsmentioning
confidence: 99%
“…These networks are built upon co-citations, bibliographic couplings, and collaborations among journals, scholars, and specific works [21]. CiteSpace (6.2.R4) serves as an information visualization software tool primarily employed for the measurement and analysis of scientific knowledge data [22]. In this paper, the raw data were imported into the VOSviewer (1.6.18) and CiteSpace (6.2.R4) software to visualize the structure of knowledge, including the research background statistics, network visualization, burst detection, and overlay visualization, to address research objective 1.…”
Section: Phase 5: Macro-quantitative Analysismentioning
confidence: 99%
“…The Tarim River, the longest inland river in China, flows through the desert, fed by melting snow from Tianshan Mountains [160]. Ejina Banner in Inner Mongolia has had a P. euphratica tree growing there for over 800 years [2,161,162]. The locals refer to it as a "sacred tree."…”
Section: Mechanism Of Abiotic Stress Tolerance In P Euphraticamentioning
confidence: 99%
“…Research suggests that P. euphratica can adapt to severe atmospheres by regulating tolerance genes, particularly in leaves related to photosynthesis. Recent applied research, such as the improved tobacco drought tolerance, highlights the importance of gene applications and techniques in enhancing P. euphratica's resilience to drought [2]. It has been demonstrated that genes increase stress tolerance by influencing physiological morphology through the study of the molecular control mechanisms of leaf morphology and physiological alterations in P. euphratica.…”
Section: Conclusion and Future Research Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation